Enteroaggregative Escherichia coli: An Emerging Enteric Food Borne Pathogen. (28th February 2010) - Kaur, P.; Chakraborti, A.; Asea, A.
Abstract : Enteroaggregative Escherichia coli (EAEC) are quite heterogeneous category of an emerging enteric pathogen associated with cases of acute or persistent diarrhea worldwide in children and adults, and over the past decade has received increasing attention as a cause of watery diarrhea, which is often persistent. EAEC infection is an important cause of diarrhea in outbreak and non-outbreak settings in developing and developed countries. Recently, EAEC has been implicated in the development of irritable bowel syndrome, but this remains to be confirmed. EAEC is defined as a diarrheal pathogen based on its characteristic aggregative adherence (AA) to HEp-2 cells in culture and its biofilm formation on the intestinal mucosa with a "stacked-brick" adherence phenotype, which is related to the presence of a 60 MDa plasmid (pAA). At the molecular level, strains demonstrating the aggregative phenotype are quite heterogeneous; several virulence factors are detected by polymerase chain reaction; however, none exhibited 100% specificity. Although several studies have identified specific virulence factor(s) unique to EAEC, the mechanism by which EAEC exerts its pathogenesis is, thus, far unknown. The present review updates the current knowledge on the epidemiology, chronic complications, detection, virulence factors, and treatment of EAEC, an emerging enteric food borne pathogen.